2021
DOI: 10.1002/ange.202108937
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Local Electron Density of Iron Single Sites by Introducing Nitrogen Vacancies for Efficient Photo‐Fenton Process

Abstract: The activity of heterogeneous photocatalytic H 2 O 2 activation in Fenton-like processes is closely related to the local electron density of reaction centre atoms. However, the recombination of electron-hole pairs arising from random charge transfer greatly restricts the oriented electron delivery to active center. Here we show a defect engineered iron single atom photocatalyst (Fe 1 -N v /CN, single Fe atoms dispersed on carbon nitride with abundant nitrogen vacancies) for the activation of H 2 O 2 under visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The as-synthesized Cu/NC-MMT also displayed a great superiority in both apparent reaction rate constant ( k obs , min −1 ) and mass activity of monatomic Cu (normalized k obs , min −1 g −1 Cu) for Fenton-like catalysis over numerous state-of-the-art reports, including Cu-C 3 N 4 , Cu 5 /FeS 2 , CoFe 2 O 4 /MoS 2 , and Fe 1 -NV/CN ( SI Appendix , Fig. S32 and Table S7 ) ( 44 , 49 51 ). Other factors such as pH, temperature, concentration, toxicity, and stability, which might affect the technical reliability, were further considered ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The as-synthesized Cu/NC-MMT also displayed a great superiority in both apparent reaction rate constant ( k obs , min −1 ) and mass activity of monatomic Cu (normalized k obs , min −1 g −1 Cu) for Fenton-like catalysis over numerous state-of-the-art reports, including Cu-C 3 N 4 , Cu 5 /FeS 2 , CoFe 2 O 4 /MoS 2 , and Fe 1 -NV/CN ( SI Appendix , Fig. S32 and Table S7 ) ( 44 , 49 51 ). Other factors such as pH, temperature, concentration, toxicity, and stability, which might affect the technical reliability, were further considered ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is in good agreement with the aforementioned PL experimental results. In addition, the LUMOs in the Co-and Fe-doped g-C 3 N 4 are distributed in the corresponding metal element sites, indicating that the photogenerated electrons can directly interact with these sites, 12 thus realizing the synergy between photocatalysis and Fenton-like catalysis.…”
Section: Cyclic Performancementioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ), a conjugated polymer with semiconductor properties that can be excited by visible light, has shown great application potential in various environmental and energy catalysis fields. In addition, the N elements with lone pairs of electrons on g-C 3 N 4 can easily coordinate with metal elements to form M–N x structures, thus forming stable atomically dispersed metal active sites and inhibiting the loss of metal elements. Therefore, g-C 3 N 4 is an ideal support and platform for the fabrication and study of photo-Fenton-like catalysts. Yet, due to the limited performance of traditional catalysts, various strategies have been applied to construct an efficient photo-Fenton-like catalyst, including constructing heterojunction, doping, defect engineering, and so on. However, all of the reported works indicated that the degradation efficiency of pollutants was higher when photocatalysis and Fenton-like catalysis were employed simultaneously.…”
Section: Introductionmentioning
confidence: 99%